2012
DOI: 10.1039/c2sm25747e
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and nanoscale fluid flow on chemical channels

Abstract: We study the time evolution and driven motion of thin liquid films lying on top of chemical patterns on a substrate. Lattice-Boltzmann and molecular dynamics methods are used for simulations of the flow of microscopic and nanoscopic films, respectively. Minimization of fluid surface area is used to examine the corresponding equilibrium free energy landscapes. The focus is on motion across patterns containing diverging and converging flow junctions, with an eye towards applications to lab-on-a-chip devices. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 82 publications
(162 reference statements)
0
9
0
Order By: Relevance
“…where and ̅ denote the corresponding components. Using MCMP models to study multiphase flows involving multi-bubble/droplet systems is more popular than SCMP models, and such studies can be found in reference [29][30][31][32][33][34][35]. However, the MCMP always suffers the limitation of increasing the density ratio and kinematic viscosity ratio [5], which restricts its application to a large extent.…”
Section: Introductionmentioning
confidence: 99%
“…where and ̅ denote the corresponding components. Using MCMP models to study multiphase flows involving multi-bubble/droplet systems is more popular than SCMP models, and such studies can be found in reference [29][30][31][32][33][34][35]. However, the MCMP always suffers the limitation of increasing the density ratio and kinematic viscosity ratio [5], which restricts its application to a large extent.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical description and numerical simulation of wetting processes on micro-, meso-and macroscales is in the case of simple liquids on inert solid substrates quite well developed. The range of approaches includes Molecular Dynamics (MD) simulations [14,18,31], lattice Boltzmann simulations [18], phase-field models [74], classical hydrodynamics (Navier-Stokes equations) [35,36] and asymptotic approaches as mesoscopic thin-film (or long-wave) models [13,45]. Comparative studies, parameter passing approaches and consistency conditions connect these approaches into a multiscale framework [18,35,49,68,70].…”
Section: Introductionmentioning
confidence: 99%
“…The range of approaches includes Molecular Dynamics (MD) simulations [14,18,31], lattice Boltzmann simulations [18], phase-field models [74], classical hydrodynamics (Navier-Stokes equations) [35,36] and asymptotic approaches as mesoscopic thin-film (or long-wave) models [13,45]. Comparative studies, parameter passing approaches and consistency conditions connect these approaches into a multiscale framework [18,35,49,68,70]. In macroscopic hydrodynamic models, polymer brushes are often considered as flexible (viscoelastic) layers without adaptability [32].…”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, surfaces with wettability gradients and surfaces with an unsymmetrical structure can usually efficiently aid the unidirectional motion of the liquid. 10,11 However, the transport of the liquid droplet in the above mentioned studies is dependent on an external source or on the surface heterogeneity. 12 In a number of industrial processes, it has been observed that a bridge of liquid is formed between two solid surfaces.…”
Section: Introductionmentioning
confidence: 99%